Coal-based synthetic natural gas vs. imported natural gas in China: a net energy perspective. (10th September 2016) - Kong, Zhaoyang; Dong, Xiucheng; Liu, Guixian
Abstract: China has two choices to meet the gap between its gas demand and supply in the short term: coal-based synthetic natural gas and imported natural gas. China currently faces the following question: between coal-based synthetic natural gas and imported natural gas, which is the better choice for China? To provide a reference for policy makers and investors, this paper compares the energy efficiency of the Datang coal gasification project, which is the first demonstration project in China, with that of imported natural gas by an energy return on investment analysis. The results show that when the environmental inputs are not considered, the energy return on investment values of coal-based synthetic natural gas with different boundaries range from 1.7:1 to 6.9:1. The values of the total imported natural gas decreased from 14.5:1 in 2009 to 7.5:1 in 2014 and then increased to 9.2:1 in 2015. When the environmental inputs are considered, the energy return on investment values of coal-based synthetic natural gas and that of imported natural gas decrease to 1.4:1–3.4:1 and 5.9:1–9.6:1, respectively. Regardless of whether the environmental inputs are considered, imported natural gas generally has a better energy return on investment than coal-based synthetic natural gas. These results suggest that from a net energy perspective, policy makers and investors should encourage to import more natural gas and be prudent about developing the coal gasification industry. Highlights: This paper compares the EROI between SNG and ING. The EROIING equation has been improved. This paper emphasises the effect of environmental inputs on EROI. ING generally has a better EROI value than SNG.